Effect of Physician-Delivered Patient Education on the Quality of Bowel Preparation for Screening Colonoscopy. (17th December 2013) - Shieh, Tze-Yu; Chen, Ming-Jen; Chang, Chen-Wang; Hung, Chien-Yuan; Hu, Kuang-Chun; Kuo, Yang-Che; Shih, Shou-Chuan; Wang, Horng-Yuan
Abstract : Background . Inadequate bowel preparation is common in outpatients undergoing screening colonoscopy because of unawareness and poor adherence to instruction. Methods . Herein, 105 consecutive outpatients referred for screening colonoscopy were enrolled in this prospective, colonoscopist-blinded study. The patients were assigned to an intensive-education group, with 10 minutes of physician-delivered education, or to standard care. At the time of colonoscopy, the quality of bowel preparation was assessed using the Boston Bowel Preparation Scale (BBPS). The primary outcome was a BBPS score ≥5. The secondary outcomes were the mean BBPS score, insertion time, adenoma detection rate, and number of adenomas detected. Results . We analyzed 39 patients who received intensive education and 60 controls. The percentage of adequate bowel preparations with a BBPS score ≥5 was higher in the intensive-education group than in the control group (97.4% versus 80.0%; P = 0.01 ). The adjusted odds ratio for having a BBPS score ≥5 in the intensive-education group was 10.2 (95% confidence interval = 1.23–84.3; P = 0.03 ). Other secondary outcomes were similar in the 2 groups. Conclusions . Physician-delivered education consisting of a brief counseling session in addition to written instructions improves the quality of bowel preparation in outpatients undergoing screening colonoscopy.